Prostate volume is an independent predictive factor in selecting low-risk prostate patients for active surveillance - Yusim, Igor; Mazor, Elad; Elsaraya, Nimer; Gat, Roni; Novack, Victor; Mabjeesh, Nicola J. (Frontiers in Urology, 2022)
Purpose: Our study aims to confirm existing viability and to seek for additional criteria in identifying patients at increased risk of disease reclassification in prostate cancer (PCa) patients on active surveillance (AS). Materials and Methods: From January 2014 to December 2018, 114 consecutive low-risk PCa patients were enrolled in AS protocol using the Epstein criteria. Uni- and multivariate Cox proportional hazards regression models, receiver performance curves (ROC), and Kaplan-Meier analysis were performed to characterize AS criteria and identify variables that predict disease reclassification. Results: PCa was diagnosed by systematic transrectal ultrasound-guided biopsy. Mean (range) follow-up was 32.7 (12-126) months. Disease reclassification occurred in 46 patients (40%). On univariate statistical analysis prostate specific antigen (PSA) (p = 0.05), prostate volume (PV) (p = 0.022), PSA density (PSAD) (p < 0.001) and number of positive cores (p = 0.021) were significant factors for disease reclassification. On the multivariate analysis, PSAD (p < 0.001) and PV (p = 0.003) were the only statistically significant independent variables to predict disease reclassification. A PSAD cut-off of 0.16 ng/ml² and a PV cut-off of 44 ml gave a maximal area under the curve, 0.69 and 0.63, respectively. Kaplan-Meier analysis showed that the median survival free from disease reclassification during AS was almost doubled in patients with PSAD < 0.16 ng/ml2 or PV > 44 ml. Conclusions: PV and PSAD significantly predicted adverse outcomes in our patients eligible for AS. Patients with a baseline PV of fewer than 44 ml would be more likely to have disease reclassification. Therefore, we believe that PV may help to select PCa patients for AS, especially in populations where the use of mpMRI is limited.